The Influence Of Content Marketing , E-Wom And Price Perception On Tiktok Social Media On Purchase Decision Lamongan District - Azizah, Luluk Nur; Rusmawati DJ, Yunni; Najiah, Evi Fitrotun; Munna, Inesa Mahdelia Laili (UNIVERSITAS PAKUAN, 2022)
The rapid development of digital technology has made social media one of the most influential media in the consumer purchase decision process, especially young consumers. One of the social media that is currently popular is Tiktok , where all people and ages use this one application. This development has made many companies start looking at Tiktok as a platform for their marketing tools, but of course business people must know the characteristics of Tiktok and also its users. This study aims to determine the effect of Content Marketing, E- WoM and price perceptions on Tiktok social media on purchase decisions in Lamongan district. The method used in this study is a quantitative descriptive method, with the sampling technique using incidental sampling, the questionnaire used to collect data is multiple linear regression analysis. The results of this study indicate that the f Content Marketing test, E- WoM and price perceptions on Tiktok social media simultaneously and significantly influence purchase decisions. The results of the t test show that Content Marketing, E- WoM and price perceptions on Tiktok social media have a positive and significant effect on purchase decisions. The results of the coefficient of determination (R2) show that Content Marketing, E- WoM and price perceptions on Tiktok social media have an effect of 60.9% on purchase decisions. The dominant influence on the purchase decision is the E- WoM variable which has a count of 10,423